SCALE OF ATTITUDES TOWARDS THE TERM OF FREE, PRIOR AND INFORMED CONSENT (FPIC) AND THE HUMANIZATION PROCESS ON MEDICAL FIELD - Angela Maria Moreira Canuto; Arthur Correia Souza Santos; Dyego Taffarel Rosendo de Barros; Jorge Artur Pecanha de Miranda Coelho; Gustavo Henrique Silva de Souza; Rui Manoel Lopes Nunes (European Scientific Journal, ESJ, 2014)
The objectives of the following article is to develop and verify the factorial validity and the internal consistency of the Scale of Attitudes toward the Term of Free, Prior and Informed Consent (FPIC) and the Humanization Process on Medical field, based on the Theory of Planned Behaviour. The study started from an analysis of the key concepts of humanization for the purpose of giving theoretical support to the empirical research. So, for the validation process of the instrument developed, it counted with the participation of 164 Brazilian medical students [61% female], with aged 19 to 34 years old (M=22.58, SD=2.27). Thus, were proceeded the Exploratory Factor Analysis and the Cronbach’s alpha test. The results confirmed that this scale of 14 items make an one-dimensional measure which reliably predicts Attitudes, Subjective Norms, Perceived of Control and Behavioural Intention in relation to the FPIC and the humanization process. Theoretical and empirical implications of the results are discussed about the instrument developed. Thereto, it was possible to identify the total scores for each one of the components, to create an instrument that can be used to find behavioural patterns between groups, and verifying the relationship between variables through the correlation and the level of explanation of the antecedent variables as the consequential variables.